SENIOR HIGH SCHOOL TEACHERS’ MATHEMATICAL QUESTIONING ABILITY AND METAPHORICAL THINKING LEARNING - Heris Hendriana (Jurnal Infinity, 2017)
This study is designed in the form of experiment with the design of control group and posttest only aimed at investigating the role of learning that teaches metaphorical thinking in improving senior high school teachers’ mathematical questioning ability. The population of this study was senior high school teachers of mathematics in West Java province and the samples were 124 senior high school teachers of mathematics set purposively and randomly to be included into the experimental class and control class. Based on the results and discussion, it is concluded that: (1) mathematical questioning ability of the teachers who received metaphorical thinking learning is better than those who received conventional learning; (2) learning factors and KAM (Kemampuan Awal Matematis = Prior Mathematical Ability) affect the achievement of teachers’ mathematical questioning ability. In addition, there is an interaction effect between the learning and KAM in developing teachers’ mathematical questioning ability; (3) teachers’ mathematical questioning ability has not been achieved optimally on the indicators submitting problems in the form of non-routine questions and open-ended questions.